A DIGNITY CENTERED MULTIDIMENSIONAL AND DYNAMIC MODEL OF QUALITY OF DEATH WITHIN TERMINAL STATE - ŠKOLKA ENIKŐ (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. The concept of "death with dignity" represents a controversial concept, at the same time frequently used in legal settings, ethical, philosophical, literary, or death psychology domains. Renowned specialists of the field argue at the same time, that death with dignity is an artificial, useless, or even dangerous concept, respectively one of the most valuable psychological constructs with regard to quality palliative care. Several studies indicate that frequently, patients report that a loss of personal dignity leads to: hopelessness, depression, wish and even request of medical interventions for intentional shortening of life. Few studies make operational the concept of death with dignity as opposed to abundant literature on the concept of good death. In the current study, aside from a short theoretical framework of the topic, we analyze on one hand the answers given by groups of participants, students and nurses with regard to the descriptive definition of death with dignity in the case of a terminal patient. On the other hand, based on studied literature and on statistical analysis of the participants' answers, we present a multidimensional and dynamic model of death quality centered on the dignity of the terminal patient.